Forecasting the economic impact of a vacuum tube high-speed transport system in Poland - an input-output approach - Lach, Łukasz; Suder, Marcin; Kusa, Rafał; Duda, Joanna (Wydawnictwa AGH, 2021)
The aim of this paper is to specify the multiplier effects that are induced in the national economy in reference to the construction of Hyperloop lines in Poland using tunnel and trestle technology. In particular, we calculate the added value and employment growth for several industries that will contribute to the construction process. We use an input-output analysis that enables us to take the detailed structure of interindustry linkages in Poland into account. According to our results, constructing a Hyperloop infrastructure in Poland would have the greatest stimulating impact on several sectors of the Polish economy, including crude oil and natural gas, metal ores, other mining products, building objects and construction work, products from other non-metallic raw materials, finished metal products, land and pipeline transport, and wholesale trade. However, this impact will be affected by the choice of construction technology (tunnel versus trestle). In addition, our calculations relate to particular routes of the potential Hyperloop network. This study contributes to the body of literature on transport infrastructures and public investments as well as Hyperloop technology development. Additionally, it contributes to the econometric methodology by employing an input-output analysis for forecasting the multiplier effects of constructing a Hyperloop system. This study has practical implications for the decision-making process on Hyperloop network development in the future.
Managerial Economics
Bibliogr. s. 138-141.
Keywords: vacuum tube high-speed train; Hyperloop; input-output (IO) analysis; economic development; technology development; interdisciplinary studies